ORTA BILIM BERIW MEKTEPLER QARAQALPAQSTAN TARIYXÍ PÁNINDE OQÍWShÍLARǴA TARIYXIY BILIMLERDI QÁLIPLESTIRIW USÍLLARÍ HÁM ÁHMIYETI - Tleumuratova, N.M. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of the process of formation of schoolchildren’s knowledge in history on the example of the subject "History of Karakalpakstan" and performing these tasks by teachers.
Keywords: history of Karakalpakstan; teaching methods; ways of increasing efficiency of studies